Synthesis and Characterization of Complexes of Cobalt(II), Nickel(II) and Copper(II) with 2-Pyrrolidene-m-nitroaniline and 2-Pyrrolidene-p-nitroaniline Schiff Bases and Their Biological Activity - Kumar, Mithilesh; Singh, A.K. (Asian Journal of Chemistry, 2010)
Complexes of Co(lI), Ni(II) and Cu(II) with the Schiff base ligandsPPNA (pyrrole-2-carboxaldehyde and p-nitroaniline) and PMNA (pyrrole-2-carboxaldehyde and m-nitroaniline) were synthesised and characterizedon the basis of the molar conductance, elemental analysis, IR, magneticmoment and electronic spectra. Complexes were also tested for antifungalactivity. Complexes derived from PPNA are ionic, paramagnetic and octahedral,whereas complexes derived from PMNA are non-ionic, paramagnetic,tetrahedral [Co(lI) and Cu(II)] and square-planar [NI(II)].